Analysis of stress-induced cracks in concrete and mortar under cyclic uniaxial compression. (30th October 2018) - Zhou, Man; Liao, Jiacong; An, Lin; Deng, Wenqin; Hassanein, Mostafa Fahmi; Yu, Zhiwu
Highlights: The internal circular crack appears first in cylinder specimens under compression. A unified expression is proposed to evaluate the volume strain of cylinder specimens. AE hit-rate can reflect the mechanical behavior of concrete in real time. Abstract: A series tests on concrete and mortar cylinders under cyclic uniaxial loading were carried in this study to investigate the effect of internal stress-induced cracks on their mechanical properties. It was found that the radial strain cannot be changed continuously because the internal circular cracks appear firstly inside the specimens. Moreover, a unified approach for calculating the apparent volumetric strain of the cylindrical specimens at both elastic and inelastic stages was proposed. Additionally, the Acoustic emission (AE) experimental result shows that the AE hits rate can well reflect the crack formation and propagations of the concrete specimen under the cyclic axial compression.